The Position of the Shrine’s Rector - ADAMCZYK, JERZY (Prawo Kanoniczne, 2013)
This article thoroughly presents the issue of the shrine’s rector. Firstly, the term and the necessity of the rector’s position are discussed. Secondly, the qualifications and the formation of the rector are shown. Finally, on the basis of the church regulations the tasks of the shrine’s rector are depicted.